Tindak Tutur Lokusi untuk Penguatan Karakter pada Pembelajaran Bahasa Indonesia di SMA/SMK - Suroso, Eko (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The purpose of this study was to explore the effect of the use of locutionary speech acts on character in Indonesian learning in high school / vocational school. The methods used in this study involved direct observation of students' verbal interactions and content analysis of aspects of religious character displayed in daily conversations in class. This study used qualitative research methods. The study was conducted for one month in a school where students of various grade levels were involved in learning activities. The results showed that consistent use of phatik locutionary speech acts in students' verbal interactions could contribute positively to the formation of their religious character. Students who actively use phatik expressions in daily interactions tend to show a more tolerant, caring, and respectful attitude towards religious diversity in the school environment. In addition, the learning environment colored by phatik locutionary speech acts also creates a more harmonious and friendly atmosphere, reinforcing the values of togetherness among members of the school community. The results of this study provide new insights into the potential use of phatik locutionary speech acts as a means of strengthening students' religious character and improving the quality of the learning environment in schools. The practical implication of this study is that there are recommendations for educators and policymakers to pay more attention to the important role of speech acts in shaping student character and creating a conducive learning atmosphere.